Incorporating supply chain risk management into sales and operations planning - Ros Orts,Maria (2025)
In a highly volatile and interconnected global environment, companies are increasingly exposed to disruptions such as pandemics, geopolitical conflicts, and natural disasters. These events can severely impact supply chains, especially for companies that rely heavily on external suppliers. The case company, a video surveillance technology provider, faces significant risks due to its limited bargaining power, long lead times, and highly volatile demand patterns. These challenges hamper its ability to accurately demand, plan production, and maintain operational continuity. Integrating real-time information and risk management into the sales and operations planning (S&OP) process is a critical step to improve supply chain agility and resilience. Supply chain risk management (SCRM) plays an important role in providing proactive strategies to anticipate and mitigate potential threats throughout the value chain. The objective of this thesis project is to provide a comprehensive analysis of the current state of the S&OP process within the case company and to explore how the integration of supply chain risk management can improve decision-making to mitigate supply chain disruptions.
Keywords: Sales and operations planning; supply chain risk management; disruption; forecasting.